Pemanfaatan ED-255EK Embedded Education Platform sebagai Modul Praktikum Embedded System Berbasis Linux - Ngurah Bimantara, I Gst Md; Raka Agung, I Gusti Agung Pt; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 17 No 2 (2018): (May - Agustus) Majalah Ilmiah Teknologi Elektro, 2018)
The development of embedded systems is of particular concern to the field of technology. Embedded systems have been widely applied in everyday life, such as automatic washing machines, electric stoves, radios, and so forth. So as to give indirect demands to understand the basic configuration of the application of embedded system itself. Learning about the basics of embedded system application can be done using ED-255EK Embedded Education Platform. ED-255EK is powered by an Intel XScale PXA255 CPU that is compatible with ARM Version 5TE ISA, Linux operating system, adopts RISC super-pipeline, and operates at 200/300/400 Mhz with low power consumption. How to operate ED-255EK is to configure the operating system first, such as package upgrades, network configuration and serial communication. Followed by configuration on ED-255EK which includes downloading file system and setting IP Address. The final step is the configuration of the module, which includes the installation of driver files and application programs, so that the input data provided will be displayed on the ED-255EK module and serialized also displayed on the laptop screen. The modules used are LED, LCD, DOT-Matrix, FND, Key-pad, DIP-Switch, Motor Stepper, IrDA, RF, and uWave modules .